Strain fields adjacent to bone-implant interfaces: strain field analysis using digital image correlation techniques - Ribeiro, J.E. (2012)
When using conventional surface strain measurement techniques (e.g. strain gauges, dial gauges), the measurement of deformations within cancellous bone is frequently hampered by the material’s highly porous structure and poor mechanical properties. Although detailed strain maps derived from actual experimental data have the potential to resolve many questions concerning the mechanics of cancellous bone, the traditional method of producing maps through measurements with optical techniques has been applied infrequently in its study of this material.